Alumni in touch: 30 March 2023 - Charles, Crystal Charlene; Hendry, Angelyca; Sahya, Aeimysyariza; Gordon, Theresa Seri; Norsalim, Suriani; Jack, Suriani (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Alhamdulillah, in the name of Allah, we would like to thank and express our gratitude to Allah SWT for blessing us with the ability to finish this assignment. With our perseverance and hard work, we finally succeeded in finishing this Management of Business Records project. The time spent in researching and debating the concepts was worthwhile. First of all, we would like to express our gratitude to Ms. Suriani Binti Jack, an IMR652 lecturer at University Teknologi Mara Kampus Samarahan in Sarawak, who taught our Management of Business Records (IMR652) course. She had given us instructions on how to finish this task. She always reminds the students and provides instructions on how to do this assignment. Then, we would want to express our gratitude to all of our friends for their assistance and ideas. They also offered us ideas and a helping hand. Many people, especially those on our team, have provided valuable feedback on this work, inspiring us to enhance it. Without the hard work and cooperation of our group members, we won't be able to do this mission. The members of the group are Aeimysyariza, Angelyca, Suriana, Theresa, and Crystal. Finally, we would want to express our gratitude to our parents who have consistently prayed for us and taken the time to understand our problems. We anticipate receiving and completing our assignment. We had put in effort and acknowledgement in our hunt for knowledge and concepts. We hope it was worth it.